Metode Al-Miftah Lil Ulum Sidogiri Sebagai Solusi Cepat dalam Pembacaan Kitab Kuning - M. Yunus; Mohammad Asrori; Parmujianto (EduInovasi: Journal of Basic Educational Studies, 2025)
One of the important parts of teaching Islam in Islamic boarding schools is reading the yellow book. However, the complexity of the classical Arabic language used in these books, along with the limited amount of time to study it thoroughly, is a major problem often faced by santri. The Sidogiri Islamic Boarding School developed the Al-Miftah lil Ulum method, which helps speed up the reading of the yellow book without reducing understanding of the material contained therein. This method uses the knowledge of nahwu and sharaf as a basis for understanding the structure of the Arabic language, and also uses speed reading techniques, which allows students to understand the text thoroughly in a shorter time. This research aims to teach the use of the Al-Miftah lil Ulum method to speed up the reading of the yellow book at the Sidogiri Islamic Boarding School Branch and how this impacts understanding of the material. This research uses a case study method and uses observation, interviews and documentation to collect data. The results show that the use of the Al-Miftah lil Ulum method increases the speed of reading the yellow book at the Sidogiri Islamic Boarding School. Apart from that, this method also reduces the linguistic difficulties that santri/pupils often face when reading classical Arabic books, thereby increasing learning efficiency. It is estimated that this research will provide new insight into the importance of mastering the basics of Arabic and help develop a faster and more effective method of learning the Yellow Book at the Sidogiri Islamic boarding school.